Perumusan Strategi Bisnis Untuk Menghadapi Peraturan Terkait Pasokan Batubara Dalam Negeri: Studi Kasus PT ABC - Fathia Noor Rahma; Nila Armelia Windasari; Widhyawan Prawiraatmadja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to formulate the right strategy for coal mining company (case study of PT ABC) in response to regulation. To ensure the stability of the domestic coal supply for national electricity and fuel or raw materials for domestic industry, the Decree of MEMR has been issued to regulate about the obligation to prioritize domestic coal supply and to determine coal sales price for domestic market. This research uses qualitative methods to identify the current situation, formulating, and proposing a new strategy. VRIO analysis and PESTEL analysis is conducted to analyze internal and external factors, respectively. The business strategies to answer the problem will be formulated based on the results of the internal and external analysis as well as the results of the interviews with the relevant stakeholders. The results shows that short-term and long-term strategies should be implemented, including to optimize the sales of coal products with the specifications that are suitable with the domestic market, acquire potential new customers from smelters industry, and encourage employees training to build compliance awareness as well as to maintain good relationship with the government. Long-term strategy namely coal gasification to produce methanol or DME products should also be explored. Keywords: Domestic Coal Supply, Domestic Coal Sales Price, Supply Assignment, Regulation, Business Strategy